Characterization of black carbon in an urban-rural fringe area of Beijing. (April 2017) - Ji, Dongsheng; Li, Liang; Pang, Bo; Xue, Peng; Wang, Lili; Wu, Yunfei; Zhang, Hongliang; Wang, Yuesi
Abstract: Measuring black carbon (BC) is critical to understand the impact of combustion aerosols on air quality and climate change. In this study, BC was measured in 2014 at a unique community formed with rapid economic development and urbanization in an urban-rural fringe area of Beijing. Hourly BC concentrations were 0.1–33.5 μg/m 3 with the annual average of 4.4 ± 3.7 μg/m 3 . BC concentrations had clear diurnal, weekly, and seasonal variations, and were closely related with atmospheric visibility. The absorption coefficient of aerosols increased while its contribution to extinction coefficient decreased with the enhancement of PM2.5 concentration. The high mass absorption efficiency (MAE) of EC was attributed to a combination of coal combustion, vehicular emission and rapidly coating by water-soluble ions and organic carbon (OC). BC concentrations followed a typical lognormal pattern, with over 88% samples in 0.1–10.0 μg/m 3 . Low BC levels were mostly bounded up with winds from north and northwest. Coal combustion and biomass burning were closely associated with severe haze pollution events. Firework discharge had significant UV absorption contribution. During the Asia-Pacific Economic Cooperation (APEC) forum in November 2014, air quality obviously improved due to various control strategies. Graphical abstract: Highlights: BC was measured in 2014 in an urban-rural fringe area of Beijing. BC concentrations had clear diurnal, weekly, and seasonal variations, and closely related with atmospheric visibility. b ab of aerosols increased but its contribution to b ext decreased with increasing of PM2.5 concentrations. Abstract : This study provides evidence that coal combustion and biomass burning sources still play an important role in BC concentrations in an urban-rural fringe area of Beijing.